Bentuk Penyajian Tari Sewa dalam Acara Pesta Perkawinan di Jorong Gando Nagari Paninggahan Kecamatan Junjung Sirih Kabupaten Solok - Arif Agustakdir Rahman; Herlinda Mansyur (SENDRATASIK UNP, 2023)
The research aims to reveal and describe the form of presentation of the Sewa Dance in Jorong Gando Nagari Paninggahan, Junjung Sirih District, Solok Regency. This type of research is qualitative research with descriptive methods. The instrument for this research is the researcher himself and is assisted by supporting instruments such as stationery, camera and cellphone. The data in this research uses primary data and secondary data. Data collection techniques were carried out using literature study, observation, interviews, and documentation techniques. The data analysis steps are carried out by collecting data, describing the data and concluding the data. The results of the research show that the presentation of the Sewa Dance in Nagari Paninggahan consists of movement, floor design, dancers, music, make-up and costumes, props, place and contextual performance time at a wedding party. There are 12 types of Sewa dance movements, but at the wedding ceremony, only 5 (five) types of movements are performed. Each of the five types of movements has a name, namely the Ciek Tusuak Siku Step, the Duo Tusuak Gasiang Step, the Tigo Tusuak Dado Step, the Ampek Sambuik jo Rabuik Pisau Step, and the Limo Kepoh Kaki Step.